First records of the subfamilies Bethylinae (Hymenoptera: Bethylidae) and Cleptinae (Hymenoptera: Chrysididae) in Upper Cretaceous amber from France. (31st December 2016) - Cockx, Pierre F.D.; McKellar, Ryan C.; Perrichot, Vincent
Abstract: Two new genera and species of fossil chrysidoid wasps belonging to the families Chrysididae and Bethylidae are described from Charentese (Fouras Bois-Vert and Archingeay) lower Upper Cretaceous amber of France. New taxa include: Sphaerocleptes neraudeaui n. gen. et sp., and Nucifrangibulum carentonensis n. gen. et sp. A new bethylid wasp is also described but left in open nomenclature. These findings are the first records of the subfamilies Cleptinae and Bethylinae in these deposits and time interval. The implications of these discoveries, and the features shared with previously known taxa are discussed.